The Effect Of Nutritional Status On The Treatment Outcome Of Calcium Channel Blockers In Hypertensive Elderly Patients In Community Health Centers In Bandung - Safira, Falah
Hypertension is the most prevalent disease, especially in elderly. For its treatment, Calcium Channel Blockers (CCBs) is one of antihypertension groups which has a widespread use in Indonesia, including in elderly group, and drug that included in this group generally has a high plasma protein binding. Elderly is in a high risk for nutritional problem, related with changes of physiological and body composition which can influence nutritional intake. Malnutrition ,which can be experienced by elderly, can lead to a decrease in protein binding of a drug, and theoretically, can increase the free fraction of drug as well as increase drug toxicity. This study was conducted to observe and evaluate the relationship between nutritional status with the outcome of treatment of hypertensive elderly patient, who use calcium channel blockers drug. This research was a descriptive and observational study which was conducted concurrent and retrospectively in Puskesmas Puter, Jayagiri, and Ciumbuleuit. The relationship between nutritional status and outcome of the treatment using CCBs, were tested by observed the possible adverse drug reactions (ADRs) of CCBs, and also by used independent t-student analysis methods toward the decrease of blood pressure of normal nutritional patient group and at risk of malnutrition and malnutrition group. The results showed no significant difference in reduction of systolic and diastolic blood pressure between nutritional status groups, both in the group of stage I and stage II hypertension, at the 0.05 significance level. However, there was a statistically significant difference between nutritional groups in reduction of systolic blood pressure in stage 2 hypertension group (P=0.06), at significance level of 0.10, where the average decrease in systolic blood pressure at normal nutrition group was larger than the group at risk of malnutrition and malnutrition. Possible ADRs of CCB occured in both of nutritional status groups. In normal nutrition status, ADRs included dizziness 39.53%; headache 13.95%; muscle cramps 13.95%; weakness 11.63%; abdominal pain 11.63%; pruritus 9.30%; fatigue 4.65%; skin rashes 4.65%; and dyspepsia 4.65%. Meanwhile, in at-risk of malnutrition and malnutrition group, ADRs included dizziness 65.71%; weakness 22.86%; abdominal pain 14.29%; muscle cramps 11.43%; headache 8.57%; fatigue 5.71%; pruritus 5.71%; skin rashes 2.86%; and dyspepsia 2.86%. There were another ADRs that only occured in at risk of malnutrition and malnutrition group, peripheral edema (5.71%) and male sexual dysfunction (2.86%). However, it is necessary to effectively control the use of calcium channel blockers drugs, especially in patients who at risk of malnutrition or malnutrition, to prevent possible ADRs.